The Effect of the Loading on Dynamic Stability and Scapular Asymmetry - Mohammad Hassan Azarsa; Azadeh Shadmehr; Shohreh Jalaei (Shiraz University of Medical Sciences, 2014)
Background: Scapular stabilization and neuromuscular control provide an important parameter to characterize shoulder function during dynamic activities. Many studies have confirmed the effect of the loading on scapular position and scapulohumeral rhythm. Therefore, the evaluation of stabilizer muscles involvement in scapular asymmetry may assist in the development of clinical examination and rehabilitation program. The aim of this study was to evaluate the effect of loading on dynamic stability and scapular asymmetry in basketball players. Methods: Thirty healthy male basketball players aged between 20 to 31 years old were tested. The linear distance between scapular inferior angle and T7 spinous process was measured using a caliper in 90 degrees of unloaded scaption and with 1, 2 and 4 kg loading. The difference of distances of two sides in the above 4 positions was analyzed. Results: The amount of distances difference in two sides with 1 kg loading was minimal (9.36 mm). This difference increased to 10.19 mm and 12.22 mm, with increasing the loading to 2 and 4 kg respectively; although the 4 positions of the test did not show significant differences in distances difference (P>0.05). Conclusion: This study shows that dynamic stability of the scapula is dependent on the role of muscles, so that with increasing load on the muscles, the scapular asymmetry is more pronounced.